Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Politiques de l'histoire: Gay New York et l'historiographie homosexuelle aux États-Unis - Fassin, Éric (Actes de la recherche en sciences sociales, 1998)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Des mots, des pratiques et des risques : la gestion différenciée de la parole et de la prévention du VIH chez des hommes à comportements bisexuels en France - Mendès-Leite, Rommel; Deschamps, Catherine (Sociologie et sociétés, 1997)
Cet article présente une partie des résultats de deux recherches socio-anthropologiques réalisées en France auprès d'hommes ayant des rapports sexuels avec des hommes et des femmes, indépendamment de leur identité socio-sexuelle. Les analyses portent d'abord sur les perceptions différenciées de la sexualité et sur ses conséquences en matière de restitution du sens, et ensuite sur la gestion des comportements préventifs. Ainsi il apparat!, au travers d'une relecture des notions de " multipartenariat ", de " sexe occasionnel " ou de " fidélité ", que le principal lieu de rupture dans la gestion des risques vin est avant tout dépendant de la variable sexe des partenaires sexuels, quand bien même la compréhension de ce mécanisme ne se réduit pas à une opposition basique entre hommes et femmes.
Keywords: 1900-1999; VIH; analyse différenciée selon les sexes -ADS+; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire et politique; hétérosexisme; justice sociale; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité masculine; sociologie; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Un sujet inclassable? approches sociologiques, littéraires et juridiques des homosexualités - Mendès-Leite, Rommel (Université, 1995)
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droits; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Bisexuality and the challenge to lesbian politics: Sex, loyalty, and revolution. - Rust, Paula C. (The Cutting Edge: Lesbian Life and Literature Series, 1995)
Le sujet de la bisexualité continue de diviser la communauté lesbienne et gay. Lors des marches des fiertés, dans des films comme Go Fish, lors de conférences universitaires, le rôle et le statut des bisexuels sont âprement contestés. Au sein des communautés lesbiennes, constituées pour soutenir les lesbiennes dans une société patriarcale et hétérosexiste, les femmes bisexuelles sont souvent perçues comme une menace ou comme une faiblesse politique. Les femmes bisexuelles se sentent considérées avec suspicion et méfiance, voire ouvertement méprisées. S'appuyant sur ses recherches auprès de plus de 400 femmes bisexuelles et lesbiennes, sur le traitement de la bisexualité dans la presse lesbienne et gay et sur la croissance récente d'un mouvement bisexuel résolument politique, Paula Rust aborde une série de questions relatives à la politique et relations sociales entre lesbiennes et femmes bisexuelles. En remontant les racines de la controverse sur la bisexualité parmi les lesbiennes aux premiers débats féministes lesbiens des années 1970, Rust soutient que ces débats ont créé les circonstances dans lesquelles la bisexualité est devenue un défi inévitable à la politique lesbienne. Elle le retrace également, prédisant l’avenir de la politique sexuelle.
Keywords: amériques; approches et analyses; bisexualité; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; militance; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp; no. 27; 5, 1994)
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Rayon art, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Nothing mat(t)ers: A feminist critique of postmodernism - Brodribb, Somer (J. Lorimer, 1992)
Nothing Mat(t)ers est une critique féministe des théories de Foucault, Derrida et Lacan, entre autres. Somer Brodribb analyse les textes et les arguments que le poststructuralisme a désignés comme centraux, exposant ainsi la misogynie en leur cœur. Brodribb fournit une histoire des définitions du structuralisme, du poststructuralisme, de la déconstruction et du postmodernisme
Keywords: approches et analyses; cours; discours dominant; fem1000; genre; histoire et politique; identités LGBTQIA2+; inégalités; patriarcat; postmodernisme; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques

Le Sexe des sciences : les femmes en plus - Collin, Françoise (Autrement, 1992)
Les femmes n'aiment pas les sciences. Les sciences n'aiment pas les femmes." Cette opinion repose sur un postulat : les femmes seraient tout entières du côté de l'intuition et de la sensibilité, les sciences du côté d'une pure rationalité. Et si ces "évidences" séculaires, confirmées par la longue exclusion des femmes des pratiques scientifiques, n'étaient qu'une histoire d'interdits, d'obstacles, de préjugés et de pouvoir? En effet, l'entrée des femmes dans l'enceinte sacrée des sciences et des technologies et une meilleure connaissance tant des femmes que du travail scientifique remettent aujourd'hui en cause leur prétendue incompatibilité. Réponses à quelques questions, entre autres : quelles sont les conditions d'accès à l'activité et à la création scientifiques, et par quelles procédures les femmes s'en trouvent-elles encore si souvent écartées? Comment cependant les femmes ont-elles contribué et contribuent-elles au développement des sciences? Leur entrée dans ce domaine peut-elle produire des effets sur le fonctionnement du savoir, sur l'éthique ou la politique de la recherche? Bref, la science a-t-elle un sexe?
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; femmes*; histoire et politique; premier cycle; sciences; sexisme; stéréotypes; systèmes d'oppressions; thématiques

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (NRF essais, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Imagined communities: Reflections on the origin and spread of nationalism - Anderson, Benedict (Verso, 1991)
L'ouvrage mondialement connu sur les origines et le développement du nationalisme Toute l'ampleur de la réussite intellectuelle de Benedict Anderson est toujours appréciée et débattue. "Imagined Communities" reste le livre le plus influent sur les origines du nationalisme, comblant le vide qui existait auparavant dans les traditions de la pensée occidentale. Cité plus souvent que tout autre ouvrage de langue anglaise en sciences humaines, il est lu dans le monde entier dans plus de trente traductions. Rédigée avec une clarté exemplaire, cette étude éclairante retrace l'émergence de l'idée de communauté en Amérique du Sud, plutôt qu'en Europe au XIXe siècle. Plus tard, ce sentiment d'appartenance s'est formé et reformulé à tous les niveaux, de la haute politique à la culture populaire, en passant par l'imprimé, la littérature, les cartes et les musées. Suite à la montée et au conflit des nations et au déclin des empires, Anderson s'appuie sur des exemples de l'Asie du Sud-Est, de l'Amérique latine et du passé récent de l'Europe pour montrer comment le nationalisme a façonné le monde moderne.
Keywords: approches et analyses; colonialisme; communication; cours; discipline; discours dominant; fem1000; histoire; histoire et politique; identités culturelles; modernité; mémoire collective; mémoire culturelle; nationalisme; occident; politique; premier cycle; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La république des hommes: les Patriotes de 1837 face aux femmes - Greer, Allan (Revue d'histoire de l'Amérique française, 1991)
Cet article examine la dimension sexuelle de la Rébellion de 1837 dans le Bas-Canada et soutient que les femmes furent bien moins actives dans la lutte anti-gouvernementale qu'elles ne l'avaient été au XVIIIe siècle dans diverses émeutes et autres mouvements de résistance. L'explication de ce changement est liée au procès de « masculinisation » de la politique qui a lieu un peu partout en Occident à la même époque. Comme le républicain type de la première moitié du XIXe siècle, le patriote du Bas-Canada défend une conception essentiellement masculine de la citoyenneté en régime démocratique. D'autre part la conviction rousseauiste que la femme vertueuse doit se confiner dans son rôle domestique permet de comprendre les poussées occasionnelles de mysoginie contre les femmes qui affichent publiquement leur opposition au mouvement patriote.
Keywords: 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; his4550; histoire; histoire et politique; politique; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques